HAMBATAN DAN SOLUSI PEMBELAJARAN JARAK JAUH PADA ERA PANDEMI COVID-19 DI JAWA TENGAH - Arif Sofianto; Mursid Zuhri (Jurnal Pendidikan dan Kebudayaan, 2021)
Abstract: Online learning during the Covid 19 pandemic had implications for the quality of education, on the other hand it led to innovation. The objectives of this study are: 1) To analyze the condition of senior high school in the Covid-19 pandemic era in Central Java (problems and progress); 2) Identifying the readiness of teachers and schools; 3) Identifying the need for quality education; and 4) Analyze the policies needed to improve the quality of education in the era of the Covid-19 pandemic. This research is descriptive, mixed method approach, qualitative and quantitative. This research involving 260 informants (principal, teachers, parents, and students). This study also used a survey method involving 84 principals, 831 teachers, 4,124 parents and 10,048 students. The data collection instruments were questionnaires and FGD. Qualitative analysis uses an interactive model developed by Miles and Huberman, quantitative analysis is descriptive, namely mean and percentage. The conclusions of this study: First, education in the Covid-19 pandemic era with a home learning strategy (daring) faces the problem of lack of facilities and infrastructure, mastery of technology, quota/internet data packages, internet network/signal. The advantages are increased mastery of technology, learning innovation, introduction of new methods, time/ energy/cost efficiency. Second, many teachers were not ready, but schools had also prepared adequate facilities, and encouraged new innovations. Third, what is needed to realize quality education through increasing the capacity of teachers, subsidizing facilities and infrastructure, improving the education system, and learning innovation. Fourth, the policy required is the implementation of a blended learning system, e-learning/LMS, curriculum adjustments, and encouraging innovation.